PENGARUH REFORMASI ADMINISTRASI PAJAK DAN MORALITAS PAJAK TERHADAP TINGKAT KEPATUHAN PAJAK (SURVEY PADA WAJIB PAJAK ORANG PRIBADI DI BANDUNG) - Riri Rumaiza (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2018)
Today, taxation is an important issue. There are many literatures has been studied about taxataion issues, especially tax compliance. Tax reform has been held by Direktorat Jenderal Pajak which has purpose to increasing the taxpayers’ compliance toward their obligations as taxpayers’. The effects of the tax reform have gained increasing attention, beside there is taxpayers’ behaviour toward to their obligations as taxpayers’ as known as tax morale. This research’s purpose is to find out the effects of tax reform and tax morale to the level of tax compliance. This research analyses the effect of tax reform and tax morale to the level of tax compliance. The survey took place in Bandung, with the analysis unit is personal tax payers’ at Bandung. Number of samples in this research is 227 taxpayers. Data collection technique are performed through literature studies and questionnaire, while Structural Equation Modeling (SEM) is used for data analysis techniques. The findings of the research shows that : (1) tax reform can be best explained by dimension of simplification of tax code factor and fairness factor, and tax morale can be best explained by dimension of economic factor, (2) there is an effect of tax reform to the tax compliance, while fluctuationin tax compliance is in accordance with tax reform, (3) tax morale effecting tax compliance significantly and positively, (4) tax reform and tax morale collectively effecting tax compliance, in which tax morale has more impact in effecting tax compliance than tax reform.